Luminescence of Eu2+-vc- dipoles and their associates in CsI:Eu crystals; Journal of Luminescence; Vol. 132, iss. 9 - Yakovlev V. Yu. Viktor Yurjevich; Trefilova L. N. Larisa Nikolaevna; Мелешко А. А. Анна Алексеевна; Ovcharenko N. N. Nikolay Nikolaevich (2012, 2012)
Title screen